Postoperative blood glucose increase can predict all-cause mortality within 3 months after successful interventional recanalization in patients with acute large vessel occlusion cerebral infarction - Wensheng Zhang; Yajie Liu; Hongxing Zhou; Jie Li; Weifang Xing; Kaifeng Li; Yudi Li; Xiongjun He; Li Ling; Jinzhao He (Diabetology & Metabolic Syndrome)
Abstract Aims To evaluate whether postoperative blood glucose increase (BGI) can serve as a predictive indicator for all-cause mortality within 3 months in patients with acute cerebral infarction with large vessel occlusion. Methods BGI was defined as fasting blood glucose levels higher than preoperative random blood glucose levels on the first morning after surgery. A retrospective analysis was conducted on the clinical data of patients with acute cerebral infarction due to anterior circulation large vessel occlusion in two centers from January 2019 to November 2023, who successfully underwent interventional recanalization. A multivariable Cox regression was performed to determine independent factors of all-cause mortality after successfully interventional recanalization. Results A total of 321 patients were included, of which 73 patients (22.74%) had BGI. The all-cause mortality rate within 3 months after surgery in BGI patients was higher than that in non BGI patients (24.66% vs. 3.23%, P < 0.001). The Kaplan-Meier analysis showed that patients with BGI had a higher postoperative mortality rate at 3 months (P < 0.001). After adjusting for potential covariates, multivariable analysis showed a significant correlation between BGI and 3-month postoperative mortality rate (adjusted HR: 5.694, 95%CI: 2.379–13.626, P<0.001). The area under the ROC curve predicted by BGI, preoperative ASPECT score, and a combination model including BGI and ASPECT score for all-cause mortality within 3 months after surgery were 0.753, 0.762 and 0.853 respectively. Conclusion BGI may be a relatively good indicator for predicting all-cause mortality within 3 months after successful interventional recanalization in patients with acute cerebral infarction due to large vessel occlusion, and the predictive efficacy of the combination model including BGI and ASPECT score is higher.